2023
DOI: 10.3390/nu15092100
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline, Intestinal Fatty Acid-Binding Protein and the Acute Gastrointestinal Injury Score as Predictors of Gastrointestinal Failure in Patients with Sepsis and Septic Shock

Abstract: Gastrointestinal (GI) failure can be both a cause of sepsis and a consequence of the systemic pro-inflammatory response in sepsis. Changes in biomarkers of enterocyte damage, citrulline and I-FABP (intestinal fatty acid binding protein), may indicate altered intestinal permeability and damage. The study group consisted of patients with sepsis (N = 28) and septic shock (N = 30); the control group included patients without infection (N = 10). Blood samples were collected for citrulline and I-FABP and a 4-point A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“… 4 A study found that a higher AGI score was associated with an increase in sepsis mortality. 27 Moreover, changes in gut microbiota are associated with the severity of AGI in sepsis. 28 At present, there are few studies on early prediction of sepsis complicated with AGI, and there is a lack of effective biomarkers for early prediction and diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 4 A study found that a higher AGI score was associated with an increase in sepsis mortality. 27 Moreover, changes in gut microbiota are associated with the severity of AGI in sepsis. 28 At present, there are few studies on early prediction of sepsis complicated with AGI, and there is a lack of effective biomarkers for early prediction and diagnosis.…”
Section: Discussionmentioning
confidence: 99%